BEPS Multilateral Convention Ratification for the Russian Tax System - Kupriyanov, Alexander S. (International Journal of Psychosocial Rehabilitation, 2020)
Purpose – As the aim of the current research is a scientific understanding of the MLI BEPS provisions and their influence on the domestic tax system in order to avoid their ambiguous perception and practical application. Design/Methodology/Approach – This paper analyzes of the consequences of the erosion of the tax base, the anti-evasive tools and strategies proposed in the implementation MLI BEPS. The general scientific dialectic approach helps to set the patterns and interconnection of the causes of the international tax instrument BEPS and the consequences of its ratification by the Russian Federation. Findings – Due to a vague tax system the income loss of the different countries, including Russia, gives a possibility to the unscrupulous companies to evade taxes. In practice the significant practical problems arise in connection with expanding the arsenal of protective measures for DTAA in states ratifying MLI BEPS. Originality/Value – Since October, 1 2019, the Multilateral Convention’s provisions have come into effect for the Russian Federation. Despite the fact that the Multilateral Convention is related to the documents of the soft force its implementation will become to be a base to correct the country’s legislation on the issue of the prospects for its economic development and also to withdraw the multinational corporations from low-tax jurisdiction and to terminate their usage of benefits and advantages.